2018
DOI: 10.1002/ddr.21460
|View full text |Cite
|
Sign up to set email alerts
|

Design, graph theoretical analysis, density functionality theories, Insilico modeling, synthesis, characterization and biological activities of novel thiazole fused quinazolinone derivatives

Abstract: Hit, Lead & Candidate Discovery A series of 2‐(2‐substituted benzylidenehydrazinyl‐2‐oxopropyl)‐3‐(4‐[4‐oxo‐2‐phenylthiazolo din‐3‐yl]phenyl)quinazolin‐4(3H)‐one 7a‐7l were synthesized and characterized by IR, 1H‐NMR, 13C‐NMR, mass spectroscopy and elemental analyses. In this present study, the density functionality theory was performed to identify drug stability. Further we introduced graph theoretical analysis by utilised Kyoto Encyclopedia of Genes and Genomes (KEGG) database and Cytoscape software to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A series of quinazolinone containing thiazolidin‐4‐one derivatives 42 reported by Saravanan and co‐workers were screened for their anticonvulsant activity by using MES and subcutaneous pentylenetetrazole (scPTZ) test at a dose level of 30, 100, and 300 mg/kg at 0.5 hr and 4.0 hr time interval [65] . The acute toxicity studies of the screened compounds showed that they were not toxic and well‐tolerated by test animals (mice) at a 2000 mg/kg dose after oral administration.…”
Section: Biological Activities Of Thiazolidinone Containing Heterocyclesmentioning
confidence: 99%
“…A series of quinazolinone containing thiazolidin‐4‐one derivatives 42 reported by Saravanan and co‐workers were screened for their anticonvulsant activity by using MES and subcutaneous pentylenetetrazole (scPTZ) test at a dose level of 30, 100, and 300 mg/kg at 0.5 hr and 4.0 hr time interval [65] . The acute toxicity studies of the screened compounds showed that they were not toxic and well‐tolerated by test animals (mice) at a 2000 mg/kg dose after oral administration.…”
Section: Biological Activities Of Thiazolidinone Containing Heterocyclesmentioning
confidence: 99%
“…From the optimized structure the frontier molecular orbital energies (E HOMO , E LUMO and their energy gap Eg) of Myr were derived. Using the GaussView molecular visualization programme, the obtained molecular orbital energy diagram was visualized [47].…”
Section: Density Functionality Theorymentioning
confidence: 99%
“…Kyoto encyclopedia of genes and genomes database was utilized for the study of graph theoretical analysis. The influential proteins was recognized and chosen by network of protein interaction (mtu: 00770) in homo sapiens [25][26][27][28].…”
Section: Graph Theoretical Analysismentioning
confidence: 99%